Quadriceps Tendon Autograft Harvest Technique Affects Both Graft Strength and Cross-sectional Area - Andrew S. Bi; Edouard J. Augustin; Cade C. Smelley; Morgan L. Angotti; Kofi K. Acheampong; Divesh Sachdev; Elizabeth Shewman; Adam B. Yanke (The American Journal of Sports Medicine, 2026)
Background: Bone–patellar tendon–bone (BTB) autografts have been considered the gold standard for anterior cruciate ligament reconstruction, although the popularity of quadriceps tendon (QT) autografts is increasing. Hypothesis/Purpose: The purpose of this study was to compare the ultrasound-derived cross-sectional area (CSA) and biomechanical strength of BTB and QT grafts harvested with different techniques. The authors hypothesized that ultrasound CSA measurements would be reliable and that QT grafts would be larger and stronger than BTB grafts, without differences between QT harvest methods. Study Design: Controlled laboratory study. Methods: Thirty grafts from 15 cadaveric knees included 15 BTB grafts harvested with a 9-mm double-blade scalpel, 7 full-thickness QT grafts harvested with the same 9-mm double-blade scalpel (DB-QT), and 8 QT grafts harvested with a proprietary 9-mm cylindrical QT harvester (CH-QT). CSA was measured at 3 regions with ultrasound by 2 raters, followed by cyclic loading and pull-to-failure testing. Between-group differences were analyzed, and associations between CSA and biomechanical outcomes were assessed with linear regression. Results: Ultrasound CSA demonstrated good to excellent reliability (ICC 2,1 = 0.70-0.87; ICC 2, k = 0.82-0.93). CSA differed between graft types (mean ± SD; BTB, 0.44 ± 0.08 cm 2 ; CH-QT, 0.64 ± 0.10; DB-QT, 0.97 ± 0.22; all pairwise P < .01), with heterogeneous variance (Levene P = .002). DB-QT demonstrated greater CSA variability than BTB ( P = .005) and no difference in variability when compared with CH-QT ( P = .055). Maximum load and energy to maximum load differed significantly (both omnibus P < .001) with DB-QT > CH-QT > BTB, with significant post hoc differences. In paired-knee analyses, pooled QT grafts also demonstrated greater maximum displacement than BTB grafts from the same specimens. CH-QT demonstrated significantly greater variability in maximum load than BTB ( P = .002) and DB-QT ( P = .045). Mean displacement at maximum load and stiffness were similar, although variance differed. Cyclic elongation differed among grafts (omnibus P = .011), with DB-QT < CH-QT < BTB, while other cyclic measures did not differ. When grafts were pooled, CSA correlated positively with maximum load and energy to maximum load; however, within–graft type regressions were not significant. After normalization to CSA, stress and strain were similar across graft types. Conclusion: QT grafts were significantly larger and stronger than BTB, with full-thickness double-blade harvest producing the greatest CSA and load to failure. Ultrasound was a reliable tool to measure CSA, which correlated with graft strength. Clinical Relevance: QT grafts demonstrate greater structural capacity than BTB, and QT harvest technique influences graft size and strength, with double-blade harvest producing larger, stronger grafts.